EFFECT OF DIFFERENT ALLELOPATHIC MULCHES ON WEED AND YIELD OF WHEAT IN Iraq - Al-Hashimi, Sama B.; Ali, Tamara A.; Tawfiq, Arwa A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Afield study was conducted in winter 2023–2024 at the Plant Protection Directorate, Abu-Ghraib, Baghdad, Iraq using randomized complete block design (RCBD) with four replication to investigates the effects of corn or sorghum mulch alone and in combination with half dose of Time line trio herbicide on weed management, soil moisture content and wheat yield. Results indicated that using corn or sorghum mulch with 50% herbicide provided higher significant results in all test parameters just like full herbicide rate .The reduction in weed density was 95.22 and 93.20%at 60 DAS, and 91.13 and 92.32% of weedy check at 90 DAS, and the reduction in weed dry weight at 120 DAS was 98.71 and 98.91%of weedy check, respectively. Grain yield was 5.66 and 5.65 t/ha, Biological yield was17.80, 17.58 t/ha respectively. Both mulch treatments affect significantly soil moisture content. This approach could be used for weed management with the objective of conserving environment and promoting sustainable agricultural system.